Manajemen Fisioterapi Dengan Chest Therapy dan Breathing Control Pada Kondisi Covid 19: Case Report - Siti Raihani; Kurnia Kusuma Ramadhan; Umi Budi Rahayu; Ririt Ika Lestari (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by a new coronavirus that first appeared in Wuhan, China, in December 2019. Patients with COVID-19 infection have a rapid but shallow breathing pattern or tachypnea. This happens because the inflammatory process caused by the SARS-CoV-2 virus interferes with the diffusion and oxygen perfusion process of the lungs. Chest physiotherapy has been shown to be effective for improving long-term respiratory physiology. ARIR recently reported on the role of chest physiotherapy in the acute phase of COVID-19, pointing out the limitations of some procedures due to limited experience with the disease. Objective: to determine the effect of giving interventions in the form of chest therapy and breathing control in reducing shortness of breath, increasing oxygen saturation and reducing spasm in the respiratory muscles. Research Methods: carried out directly to 1 patient with the condition of Covid 19 by giving therapy 5 times. The results obtained after 5 therapy sessions showed that there was a reduction in shortness of breath, an increase in oxygen saturation, and a reduction in respiratory muscle spasm. Conclusion: it can be said that a comprehensive physiotherapy program in Covid 19 cases with chest therapy and breathing control has been shown to be able to reduce shortness of breath, increase oxygen saturation, and reduce spasm in the respiratory muscles.Keywords: Covid 19, Chest therapy, Breathing control